Towards sustainable rail mobility: emission reduction strategies for modern rail operations - Marino, Concettina; Giunta, Marinella (International Conference “Environmental Engineering”, 2026)
Railway systems represent a cornerstone of sustainable transportation, providing an environmentally efficient means of moving both people and goods. Their ability to deliver high transport capacity with comparatively low greenhouse gas (GHG) emissions, combined with their contribution to reducing road congestion, positions rail as a key pillar of modern low-carbon mobility. The ongoing electrification of rail networks further enhances these benefits by enabling the use of renewable electricity along increasingly extensive corridors. However, despite these advancements, diesel locomotives, still essential for shunting operations, regional services, and non-electrified routes, remain a significant source of environmental impacts. The resulting emissions negatively affect air quality and pose health and climate change concerns, particularly in densely populated or high-traffic railway areas. To meet tightening emission standards, the rail sector is advancing multiple decarbonization strategies, including full electrification, hybrid propulsion technologies, and the adoption of low-carbon fuels. Among these, advanced biofuels, such as biodiesel and Hydrotreated Vegetable Oil (HVO) together with hydrogen used in fuel cell or combustion-based systems, are emerging as the most promising options. Building on established methodologies for assessing rail energy use and emissions, this study develops and applies a procedure for comparing the environmental burdens of conventional diesel traction with those associated with innovative propulsion and fuel solutions across a range of railway operations. The findings confirm that renewable fuels can substantially mitigate the climate impact of rail activities, while hydrogen-powered systems offer significant potential for deep and long-term decarbonization, particularly when supported by renewable energy sources. Nonetheless, the transition to hydrogen remains challenging due to the high energy requirements of its production, the need for dedicated storage and refuelling infrastructure, and uncertainties linked to large-scale deployment. These factors highlight the necessity of a comprehensive Well-to-Wheel (WTW) assessment to fully evaluate the environmental performance of emerging alternatives and ensure that their adoption results in genuine sustainability gains.